Anticoagulation Management During ECMO: Narrative Review - Jaromir Vajter; Oksana Volod (JHLT Open)
Extracorporeal membrane oxygenation (ECMO) is a critical intervention for patients with severe respiratory or cardiac failure, requiring careful management of anticoagulation to prevent thromboembolic complications. This review examines current practices and challenges in ECMO anticoagulation, focusing on strategies, agents, and emerging insights. Unfractionated heparin (UFH) remains the most commonly used anticoagulant, monitored via activated partial thromboplastin time (aPTT) or activated clotting time (ACT). Increasing attention is given to alternative tools like anti-Xa and viscoelastic assays (VEA), which offer potentially more reliable results. Supplementation with antithrombin should be considered if levels fall below 50%–70% to optimize heparin efficacy. Low molecular weight heparin (LMWH) is occasionally used due to its predictable pharmacokinetics, though challenges in dosing and reversal limit its application. Direct thrombin inhibitors, such as bivalirudin, are valuable alternatives, particularly for patients with heparin-induced thrombocytopenia (HIT), though their cost and availability remain barriers. Anticoagulation in ECMO patients is complex, balancing the risks of thrombosis and bleeding. Factors such as patient age, underlying conditions, and ECMO-induced coagulopathies complicate management. Personalized anticoagulation protocols and point-of-care VEA are emerging as effective tools for improving therapy. Routine no-anticoagulation strategies are not recommended unless there are significant bleeding complications. Ongoing research into novel anticoagulants and the long-term impact of anticoagulation on ECMO outcomes is critical. Anticoagulation management in ECMO continues to evolve, focusing on individualized approaches, improved monitoring, and better outcomes. Standardized protocols and further research are essential for optimizing care in this high-risk population.